Immune challenge induces terminal investment at an early breeding stage in female zebra finches. (24th October 2018) - Sköld-Chiriac, Sandra; Nilsson, Jan-Åke; Hasselquist, Dennis
Abstract : Animals are usually faced with a trade-off between investing in reproduction or in survival. Although animals normally seek a compromise, they might invest most of their resources into reproduction if they feel that this may be the last reproductive event in their life. We vaccinated female zebra finches, resulting in their immune system signaling sickness. Vaccinated finches produced more eggs than controls, thus reacting as if they were making a final investment. Abstract: The "terminal investment" hypothesis proposes that individuals with low future survival prospects will gain from increasing investment in the current reproductive event even though it will reduce the chances of future reproduction even further. Such investments have previously been found to occur mainly during the late stages of the breeding event, that is, encompassing a short period of elevated parental care close to offspring independence. Our aim was to study if a simulated mild bacterial infection can induce a terminal investment already at egg laying (i.e., at an early breeding stage). Therefore, we challenged female zebra finches ( Taeniopygia guttata ) before egg laying with a tetanus-toxoid vaccine mimicking a bacterial infection. Immune-challenged females increased the total clutch mass by 20%, primarily through laying clutches that were 17% larger than control females. Although the immune-challenged females produced more eggs, they kept the same investment strategy in relation to egg laying order as did control females. Our study implies that female birds can use a nonpathogenic immune challenge as an indication of declining survival prospects, and consequently increase clutch size. These investment decisions by immune-challenged mothers are in line with "terminal investment" conducted at an early stage of breeding, challenging the traditional view that terminal investment should occur at late breeding stages.